Evaluating particle-suspension reactor designs for Z-scheme solar water splitting via transport and kinetic modeling. Issue 1 (11th October 2017) - Bala Chandran, Rohini; Breen, Sasuke; Shao, Yuanxun; Ardo, Shane; Weber, Adam Z.
Abstract : Simulations of coupled light absorption, transport and kinetics processes in a tandem, vertically-stacked particle-suspension reactor design for solar-water splitting. Abstract : Sunlight-driven water splitting to produce hydrogen and oxygen provides a pathway to store available solar energy in the form of stable, energy-dense chemical bonds. Here we investigate a tandem particle-suspension reactor design for solar water splitting comprising micron-scale photocatalyst particles suspended in an aqueous solution with soluble redox shuttles. A porous separator facilitates redox species transport between the hydrogen and oxygen evolution reaction compartments while averting gas crossover. A two-dimensional, transient model of the reactor is presented to illustrate the coupling between light absorption, interfacial electron-transfer kinetics and species transport, and their combined impacts on overall solar-to-hydrogen conversion efficiency. The volumetric reactivity of the suspended semiconductor particles is dictated by combining the (photo)current–voltage behavior of a photodiode with Butler–Volmer electron-transfer kinetics. For the first time, a quantitative approach to determine the impacts of surface-dependent redox shuttle kinetic parameters on reaction selectivity in a Z-scheme system is established. Model results provide insights on the effects of optical, transport and kinetic properties of the semiconductor particles and the redox shuttles on the overall reactor performance. Solar-to-hydrogen reactor efficiencies predicted with BiVO4 particles for oxygen evolution are at least two times larger than efficiencies achieved with wider band-gap TiO2 particles due to enhanced visible light absorption; hydrogen evolution with SrTiO3 :Rh particles was considered for both cases. Superior performance is predicted with proton-coupled electron transfer redox shuttles ( para -benzoquinone/hydroquinone and iodide/iodate) that absorb little-to-no visible light, while also facilitating operation at near-neutral pH conditions, as compared to the non-proton-coupled triiodide/iodide and iron(iii )/iron(ii ) redox shuttles. For 1 cm tall reaction compartments, diffusive species transport is fast enough to sustain reactor operation at a 1% solar-to-hydrogen conversion efficiency for both para -benzoquinone/hydroquinone and iodate/iodide redox shuttles with less than 2.2 mg L −1 of each of BiVO4 and SrTiO3 :Rh particles in the solution.